(untitled) (Research, Society and Development, 2022)
The construction of the nursing legacy is transposed by several historical, cultural, as well as socioeconomic particularities. Nowadays, in times of a pandemic, a lot has been released about nursing professionals. The following study aims to know and describe the perception of these professionals regarding the valuation, visibility and factors that influence a stigmatized image, permeated by the underestimation and devaluation of the profession. The present study is a descriptive exploratory field research, of qualitative and quantitative analysis, having as a sample population, nursing professionals in the scope of primary care, eight Basic Health Units in the city of Guaraí and two Basic Health Units in the city of Pequizeiro state of Tocantins, Brazil. When questioned about professional visibility, 30 (96.8%) stated that nursing is a devalued class, and 1 (3.2%) guarantees that the profession is valued, in terms of salary, 21 (67.7%) do not think it the salary consistent with the profession and 9 (29%) say that the salary is not consistent. Thus, the data show the dissatisfaction of these professionals due to the lack of visibility, appreciation, long working hours and the absence of a decent salary, as well as all these factors negatively influence the exercise of the function. Thus, in order to nullify the vilified image of nursing, it is inferred a greater demand for notoriety in society as well as in the media and greater autonomy, professional appreciation and fair salary in addition to better working conditions.